Propolis antibacterial and antioxidant synergisms with gentamicin and honey - Freitas, Ana Sofia (2022)
Abstract Aims Assess the antibacterial and antioxidant effects of ethanol extracts of Portuguese propolis samples when combined with gentamicin, a widely used aminoglycoside antibiotic, or with honey, collected from the same apiary as propolis. Methods and Results Using the agar dilution method and DPPH free radical scavenging assay, antimicrobial and antioxidant synergistic effects between propolis and gentamicin or honey were assessed. Synergism between propolis and gentamicin was observed for all the tested extracts and against all the indicator bacteria, with particular interest against the Methicillin Resistant Staphylococcus aureus (MRSA) with a threefold decrease of the gentamicin MIC if mixed with 25 µg ml-1 propolis. Likely to propolis and gentamicin, mixtures of sub-MIC concentrations of propolis and honey enhanced the antibacterial action of each individual natural product against the majority of the strains. However, propolis antioxidant capacity decreased along with higher honey content in the mixture. Conclusions Propolis has strong synergistic effect when combined with gentamicin, allowing the reduction of the therapeutic dose of this drug. Propolis and honey mixtures also display stronger antibacterial effect than the activity exhibited by each sample when tested individually whereas the high antioxidant capacity of propolis seems to be not affected when in combination with honey. Significance and Impact of Study When mixed with honey, propolis antioxidant potential is maintained, or just slightly reduced up to 1:1 dilution, and show synergistic antibacterial effects, allowing to optimize the use of this usually scarce natural resource. Also, considering the antibiotic resistance problem, natural beehive products, alone or in mixture, are promising alternatives to retard the outbreak of microbial resistance.